Analysis of the Hadith On Hudud Crimes: A Study of the Prohibition Alcoholic Beverages From an Islamic Legal Perspective - Aniksya Nabila Safikoh; Yardah Annissi Ahdy Sitorus (AT-TAFAHUM: Journal of Law, 2021)
This study aims to analyze hadiths related to hudud crimes, particularly the prohibition on drinking alcohol from an Islamic legal perspective. Alcohol is any type of intoxicating beverage that is prohibited in Islam because it can damage the mind and cause various negative impacts, both for individuals and society. This prohibition is not only based on the Qur'an, but also emphasized in the hadith of the Prophet Muhammad SAW, which states that everything that intoxicates is haram. The research method used is qualitative research with a library approach, through a review of related hadiths and fiqh jinayah literature. The results show that drinking alcohol is included in the category of hudud crimes that are subject to strict sanctions in the form of caning as a form of deterrent and prevention. In addition, alcohol is also seen as a source of various crimes because it can reduce a person's awareness and self-control. From an Islamic legal perspective, the prohibition of alcohol aims to maintain the mind (hifz al-'aql) as part of the maqashid sharia.